Manipulation of facet orientation in hybrid perovskite polycrystalline films by cation cascade - Zheng, Guanhaojie; Zhu, Cheng; Ma, Jingyuan; Zhang, Xiaonan; Tang, Gang; Li, Runguang; Chen, Yihua; Li, Liang; Hu, Jinsong; Hong, Jiawang; Chen, Qi; Gao, Xingyu; et al. (Nature communications, 2018)
Crystal orientations in multiple orders correlate to the properties of polycrystalline materials, and it is critical to manipulate these microstructural arrangements to enhance device performance. Herein, we report a controllable approach to manipulate the facet orientation within the ABX 3 hybrid perovskites polycrystalline films by cation cascade doping at A-site. Two-dimensional synchrotron radiation grazing incidence wide-angle X-ray scattering is employed to probe the crystal orientations in multiple orders in mixed perovskites thin films, revealing a general pattern to guide crystal planes stacking upon extrinsic doping during crystallization. Different from previous studies, this method enables to adjust the crystal stacking mode of certain crystallographic planes in polycrystalline perovskites. Moreover, the preferred facet orientation is found to facilitate photocarrier transport across the absorber and pertaining interface in the resultant PV device, which provides an exemplary paradigm for further explorations that relate to the microstructures of hybrid perovskite materials and relevant optoelectronics. Crystal facet orientations of the polycrystalline hybrid lead halide perovskite thin films play a crucial role in determining the device performance. Here Zheng et al. demonstrate effective control of the crystal stacking mode by cation cascade doping, which promotes the charge transport in the photovoltaic device.